PENGARUH TAGLINE #DIRUMAHAJA PADA IKLAN GOJEK DI INSTAGRAM TERHADAP MINAT UNTUK MENGGUNAKAN LAYANAN GOFOOD : Survei pada Followers Instagram Gojek - Dimas Panji Laksono (2020)
The tight competition encourages the companies to be smarter and creative in conducting marketing strategies. One of marketing strategy that can be used is the using of a tagline in an advertisement to strengthen and communicate a brand or product. This research was conducted to find out how much influenced the #dirumahaja tagline on Gojek ads has on the interests to use GoFood services. The sample in this study is from Instagram followers @gojekindonesia. This research uses a quantitative research approach, with survey research methods. The theory used is Elaboration Likelihood Model, namely that people in processing persuasive messages that have different ways. Based on the research results, it can be seen that there is an influence of #dirumahaja Gojek ads tagline on the interest in using the GoFood service. As many as 61.9% of Gojek's Instagram followers' interest in using the GoFood service is determined by the #dirumahaja ad tagline, and the rest (38.1%) is determined by other factors not examined.